Virtue and authenticity in civic life. Issue 1 (2nd January 2023) - Vess, Matthew; Stichter, Matt; Hicks, Joshua A.; Schlegel, Rebecca J.
ABSTRACT: A robust literature indicates that when people feel that they are expressing and aware of their true selves, they show enhanced psychological health and well-being. This feeling, commonly referred to as authenticity, is therefore a consequential experience. In this paper, we review a program of research focused on the relevance of authenticity for civic engagement. We describe how a virtuous orientation to civic engagement might make civic actions feel more authentic and how the experience of authenticity might help sustain civic behavior. We then discuss the role that education might play in fostering a deeper connection between civic engagement and the subjective experience of authenticity.